2021
DOI: 10.1108/medar-11-2020-1091
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability reporting in justice systems: a comparative research in two European countries

Abstract: Purpose That on accountability in public organizations is quite an old debate. Its introduction in judicial systems is, however, still viewed with some suspicion, due to its potential trade-off with independence and impartiality. Nevertheless, the need to respond to the demands for greater transparency and accountability has also pushed judicial organizations to establish a dialogue with a wide range of subjects. This study aims to explore the understanding and the current practices of sustainability reporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…It had published the first sustainability report five years earlier; hence, it could be defined as an early adopter in the Italian judicial system. Although it then stopped this practice, as in most cases in PSOs (Fusco et al , 2022; Farneti et al , 2019; Vinnari and Laine, 2013), it showed the willingness to resume it by being firmly convinced of its necessity in the relationship between the office and the community, thus offering a particular awareness and maturity on the topic. It was, therefore, considered an interesting research laboratory in a sector (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It had published the first sustainability report five years earlier; hence, it could be defined as an early adopter in the Italian judicial system. Although it then stopped this practice, as in most cases in PSOs (Fusco et al , 2022; Farneti et al , 2019; Vinnari and Laine, 2013), it showed the willingness to resume it by being firmly convinced of its necessity in the relationship between the office and the community, thus offering a particular awareness and maturity on the topic. It was, therefore, considered an interesting research laboratory in a sector (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…It was, therefore, considered an interesting research laboratory in a sector (i.e. the judicial one) highly under investigated in literature and a country with a fair amount of ferment in these practices, which, however, seems to have experienced a slowdown after an initial impulse (Greco et al , 2015; Farneti et al , 2019; Fusco et al , 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research into sustainability reporting of judicial systems is somewhat embryonic. Therefore, Fusco et al (2021) carry out a comparative study of the process between courts in Italy and Poland. Prior evidence reveals the justice system in Italy to be inefficient, with civil and commercial cases taking longer to resolve than the average time in other EU nations.…”
Section: Evidence From Italy and Polandmentioning
confidence: 99%
“…[9], Abela M. [10], Nasreen T., Baker R., Rezania D. [11] and others);  standardization of approaches to disclosure of information on the sustainable development of entities (de Villiers C., La Torre M., Molinari M. [12], de Villers C., Dimes R. [13] and others);  improvement of the regulatory and organizational model of preparation, collection and quality control of corporate sustainability reporting (Amoako K. O., Amoako I. O., Tuff our J., Marfo E. O. [14], Fusco F., Civitillo R., Ricci P., Morawska S., Pustulka K., Banasik P. [15], Iefymenko T., Lovinska L., Kucheriava M. [16] and others);  empirical studies of the corporate reporting practices on sustainable development by sectors and regions (Tumwebaze Z., Bananuka J., Orobia L., Kinatta M. [17], Leo D., Sfodera F., Cucari N. Mattia G., Dezi L. [18], Buallay A. [19], Alsahali K. F., Malagueno R. [20] and others).…”
mentioning
confidence: 99%